Floral Quality and Inflorescence Architecture in Olea europaea 'Arauco' (La Rioja, Argentina) - Brizuela, Maria Magdalena (2014)
Floral quality is often overlooked as being one of the key yield determinants in olive. One aspect of floral quality is the number of perfect hermaphroditic flowers with both male and female reproductive parts relative to imperfect, staminate (male) flowers. We assessed inflorescence density, number of perfect and imperfect flowers, and inflorescence architecture in the cultivar ‘Arauco’ on the north- and south-sides of six 40-year-old trees growing in a small traditional orchard with a 10×10 m planting density in Aimogasta (La Rioja, Argentina). Some complementary measurements were done in a second orchard. A trade-off was found in the first orchard between inflorescence density and floral quality with inflorescence density being less on the north side of the trees versus the south, while the number of perfect flowers showed the opposite pattern. This phenomenon led to a negative relationship between inflorescence density and percentage of perfect flowers per inflorescence. Comparing the two orchards, the well-irrigated and fertilized first orchard that received flood irrigation every two weeks and manure as fertilizer had the greatest percentage of perfect flowers at the most terminal position on the inflorescence. In contrast, the second orchard received only occasional flood irrigation and no fertilization, had fewer perfect flowers, and the perfect flowers (%) were not greater at the terminal position than more basal branch positions. As a whole, these results show that both biological factors such as inflorescence density and orchard management strongly affect floral quality in the Argentinean cultivar ‘Arauco’. Detailed experimental studies are needed to better understand the various influences on floral quality and inflorescence architecture.